„Wenn der Steuermann ruft…“ (Epiktet, Encheiridion 7) - Krämer, Benedikt (Hyperboreus, 2022)
Epictetus’/Arrianus’ Encheiridion is for the most part a lucid and readily understandable text. The precise meaning of c. 7 and its imagery, however, is still a matter of dispute. The present paper offers a reinterpretation of c. 7 which tries to link c. 7 to stoic physics and psychology on the one hand and Epictetus’ personal religiosity and his psychagogic style of writing on the other hand.